2004
DOI: 10.1126/science.1097196
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of Ca 2+ -Regulated Membrane Fusion by Synaptotagmin and SNAREs

Abstract: We investigated the effect of synaptotagmin I on membrane fusion mediated by neuronal SNARE proteins, SNAP-25, syntaxin, and synaptobrevin, which were reconstituted into vesicles. In the presence of Ca2+, the cytoplasmic domain of synaptotagmin I (syt) strongly stimulated membrane fusion when synaptobrevin densities were similar to those found in native synaptic vesicles. The Ca2+ dependence of syt-stimulated fusion was modulated by changes in lipid composition of the vesicles and by a truncation that mimics c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
404
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(438 citation statements)
references
References 22 publications
31
404
3
Order By: Relevance
“…However, recent experiments on fusion of synaptobrevin-containing liposomes are difficult to reconcile with the view of an intrinsic inactivation of the protein. Although fusion of synaptobrevin-containing liposomes with liposomes containing SNAP-25 and syntaxin is slow (Weber et al, 1998;Schuette et al, 2004;Tucker et al, 2004), the fusion rate is accelerated dramatically when the syntaxin/SNAP-25 binding site for synaptobrevin is stabilized (Pobbati et al, 2006). Thus it appears that the availability of the acceptor site rather than the intrinsic activity of membrane-anchored synaptobrevin is rate-limiting.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, recent experiments on fusion of synaptobrevin-containing liposomes are difficult to reconcile with the view of an intrinsic inactivation of the protein. Although fusion of synaptobrevin-containing liposomes with liposomes containing SNAP-25 and syntaxin is slow (Weber et al, 1998;Schuette et al, 2004;Tucker et al, 2004), the fusion rate is accelerated dramatically when the syntaxin/SNAP-25 binding site for synaptobrevin is stabilized (Pobbati et al, 2006). Thus it appears that the availability of the acceptor site rather than the intrinsic activity of membrane-anchored synaptobrevin is rate-limiting.…”
Section: Introductionmentioning
confidence: 91%
“…Although it is conceivable that differences in the protein and vesicle purification protocols may account for some of the differences (for instance, Hu et al used proteins purified by preparative denaturing SDS-PAGE for reconstitution), we have no obvious explanation for these discrepancies. Indeed, several laboratories reported that synaptobrevin-containing liposomes readily fuse with liposomes containing SNAP-25 and syntaxin, a reaction that clearly requires active synaptobrevin (Weber et al, 1998;Schuette et al, 2004;Tucker et al, 2004). Furthermore, clostridial neurotoxins readily cleave membrane-bound synaptobrevin both in liposomes and in synaptic vesicles, with toxin action requiring access to most of the cytoplasmic domain of synaptobrevin (Montecucco et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…10a) may enhance flippase activity resulting in an unfavorable local lipid environment to support fusion. CAPS, rabphilin, and Syt1 support exocytosis via interaction with PIP [53,65,79]. CAPS, a component of the synaptic vesicle priming machinery, maintains a fusion-competent vesicle pool for transmitter release [47].…”
Section: Roles For Polyphosphoinositides In Regulated Releasementioning
confidence: 99%
“…These liposomes can selectively interact with other liposomes bearing a reconstituted "vesicle," or v-, SNARE to allow selective lipid mixing (5), vesicle content mixing (6), or lysis (7,8). This reconstituted reaction shows impressive specificity for cognate SNARE pairs (9) and can be directly promoted by other fusion-regulatory factors such as synaptotagmin and calcium (10) or Sec1p (11) under conditions that minimize lysis (12).…”
mentioning
confidence: 99%